The FTO gene rs9939609 polymorphism predicts risk of cardiovascular disease: a systematic review and meta-analysis. - Chibo Liu; Sihua Mou; Chunqin Pan (PLoS ONE)
Objective Genome-wide association studies have shown that variance in the fat mass- and obesity- associated gene (FTO) is associated with risk of obesity in Europeans and Asians. Since obesity is associated with an increased risk of cardiovascular disease (CVD), several studies have investigated the association between variant in the FTO gene and CVD risk, with inconsistent results. In this study, we performed a meta-analysis to clarify the association of rs9939609 variant (or its proxies [r (2)>0.90]) in the FTO gene with CVD risk. Methods Published literature from PubMed and Embase was retrieved. Pooled odds ratios with 95% confidence intervals were calculated using the fixed- or random- effects model. Results A total of 10 studies (comprising 19,153 CVD cases and 103,720 controls) were included in the meta-analysis. The results indicated that the rs9939609 variant was significantly associated with CVD risk (odds ratio = 1.18, 95% confidence interval = 1.07-1.30, p = 0.001 [Z test], I (2) = 80.6%, p<0.001 [heterogeneity]), and there was an insignificant change after adjustment for body mass index (BMI) and other conventional CVD risk factors (odds ratio = 1.16, 95% confidence interval = 1.05-1.27, p = 0.003 [Z test], I (2) = 75.4%, p<0.001 [heterogeneity]). Conclusions The present meta-analysis confirmed the significant association of the rs9939609 variant in the FTO gene with CVD risk, which was independent of BMI and other conventional CVD risk factors.